Advantages of the Principal’s Strategy in Recruiting Prospective Students at SMA Negeri 1 Gunung Megang - Wulandari, Shintya; Harapan, Edi; Furkan, Nuril (Journal of Social Work and Science Education, 2023)
This study aims (1) to describe and analyze the principal’s strategy in recruiting New Student Admissions (PPDB) at SMA Negeri 1 Gunung Megang; (2) To describe and analyze the inhibiting and supporting factors in implementing the new student acceptance strategy (PPDB) at SMA Negeri 1 Gunung Megang. This research uses descriptive qualitative approach. This research was conducted at SMA Negeri 1 Gunung Megang with the subject of this research being the school principal. The informants of this study were Student Representatives, Chairpersons of PPDB Committees, and Teachers. Data collection techniques using observation, interviews and documentation. The results of the research to apply the principal’s strategy in recruiting prospective students at SMA Negeri 1 Gunung Megang include (1) improving and completing school infrastructure (2) Neat and comfortable school environment. PPDB socialization is carried out through the media banners, banners, brochures and social media such as Facebook and Instagram, visits to schools that are the target or target schools and PPDB socialization are also carried out during student parent meetings. The inhibiting factors in implementing the principal’s strategy in recruiting prospective students at SMA Negeri 1 Gunung Megang include too many (1). students registering and the quota accepted is limited so that the parents of students whose children are not accepted make threats to damage the school and so on (2). The existence of a very large number of students considering the limited infrastructure means that there must be support from other parties, both the government/parents and guardians.